Transcervical Thyroidectomy for Huge Posterior Mediastinal Goitre: A Challenging Case - Khandasamy Y.,; Nani Harlina ML.,; Saladina JJ.,; Rohaizak M., (Department of Surgery, UKM Medical Centre, 2015)
The decision for median sternotomy for retrosternal goiter is complex and proper consensus are lacking. Generally, it is based on clinical, radiological and intraoperative assessment. Among the few known features include primary mediastinal goiter, posterior mediastinal goiter and recurrent retrosternal goiter. We present a patient with posterior mediastinal, secondary goiter that extended until the tracheal bifurcation. The goiter was removed successfully via a low cervical incision and this was achieved by dissecting along the anatomical plane close to the thyroid capsule using blunt dissection with fingers. It is possible for these kinds of high risk retrosternal goitres to be safely removed without the need for thoracotomy when the surgery was performed along the proper plane.